2016
DOI: 10.1093/nar/gkw027
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3 circular RNA retards cell cycle progression via forming ternary complexes with p21 and CDK2

Abstract: Most RNAs generated by the human genome have no protein-coding ability and are termed non-coding RNAs. Among these include circular RNAs, which include exonic circular RNAs (circRNA), mainly found in the cytoplasm, and intronic RNAs (ciRNA), predominantly detected in the nucleus. The biological functions of circular RNAs remain largely unknown, although ciRNAs have been reported to promote gene transcription, while circRNAs may function as microRNA sponges. We demonstrate that the circular RNA circ-Foxo3 was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
1,131
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,382 publications
(1,144 citation statements)
references
References 34 publications
5
1,131
0
8
Order By: Relevance
“…Another study by the same research group showed that circ-Foxo3 could also bind to the cell cycle proteins cyclin-dependent kinase 2 (CDK2) and cyclin-dependent kinase inhibitor 1 (p21), resulting in the formation of a ternary complex. 49 The formation of this circ-Foxo3-p21-CDK2 ternary complex arrested the function of CDK2 and blocked cell cycle progression, adding support to circ-Foxo3 acting as a protein's scaffold to modulate certain cellular activities. In summary, circ-Foxo3 seems to be able to bind to many different proteins.…”
Section: Protein Interactionmentioning
confidence: 99%
“…Another study by the same research group showed that circ-Foxo3 could also bind to the cell cycle proteins cyclin-dependent kinase 2 (CDK2) and cyclin-dependent kinase inhibitor 1 (p21), resulting in the formation of a ternary complex. 49 The formation of this circ-Foxo3-p21-CDK2 ternary complex arrested the function of CDK2 and blocked cell cycle progression, adding support to circ-Foxo3 acting as a protein's scaffold to modulate certain cellular activities. In summary, circ-Foxo3 seems to be able to bind to many different proteins.…”
Section: Protein Interactionmentioning
confidence: 99%
“…17,21 Second, pioneering studies have now showed functionality of specific circRNAs in both normal physiology and disease. 18,[22][23][24][25] Third, circRNAs are cytoplasmic, whereas most (if not all) undesired splicing products accumulate at the site of transcription. 26 Fourth, circRNAs are evolutionarily conserved at both their sequence level and their pattern of expression, in particular in the brain.…”
Section: Circrnas: a New Regulation Layer Of Gene Expressionmentioning
confidence: 99%
“…CircFOXO3 inhibits cell cycle progression by forming a ternary complex with cyclin-dependent kinase 2 (CDK2) and cyclin-dependent kinase inhibitor 1 (p21). 23 CircH-IPK3 directly binds and inhibits miR-124 activity, and silencing it results in arrested cell growth. 22 In addition, we recently reported that the splicing factor muscleblind (mbl) hosts a circRNA which is involved in the auto-regulation of this RNA-binding protein.…”
Section: Circrnas: a New Regulation Layer Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, we showed that the circular RNA circ-Foxo3 could function by binding to proteins in related signal pathways. 10,11 In the present study, we used computational approach to elucidate the interaction of circ-Foxo3 with MDM2 and p53. The RING-finger domain in the carboxyl terminal of the MDM2 is known to bind RNA specifically in a sequence-specific manner, 12 whereas p53 interacts with RNA via its C-terminal regulatory domain.…”
mentioning
confidence: 99%